Über die Bedeutsamkeit linguistischen Wissens im privatwirtschaftlichen Arbeitsfeld - Iseli, Marlène (My University, 2010)
Until today, linguistics as an academic field does not aim at responding to the expectations of the job market. However, on the backdrop of an increasing interrelation of politics, economy and science, questions as to the applicability of linguistics to labour processes and the employability of linguists are raised and need to be answered. In analysing data gained in the course of 21 interviews conducted with linguists working in the private sector of economy, several issues have shown to be of major interest. This paper addresses firstly in what ways linguistics was likely to be seen as relevant for the jobs held by the various interviewees from the point of view of their employers, which is then compared to the interviewees' own evaluations on the relevance of linguistic knowledge for their daily work. On the one hand it becomes clear that there are differences between the three comparable situations in which the analysed transfer of knowledge takes place (Quereinstieg, Schnittstellenjob, "sprachperformativer Job"). One the other hand linguistic expertise in the extra-academic field seems to be most salient or approved of when it comes to language competence in text production or communicative situations, which further complicates the attempt to make linguistics transparent for non-linguists.
Keywords: Applicability of linguistics; economy; knowledge transfer; employability; job market